222k views
0 votes
How do you do this equation 16*3-(-36)/12

User Tim Ryan
by
5.8k points

2 Answers

1 vote

Answer: 51

Explanation:

16 * 3 - (-36) / 12

Multiply and divide (left to right) 16 * 3 = 48

= 48 - (-36)/12

Multiply and divide again (left to right) (-36)/12 = -3

= 48 - (-3)

Add and subtract (left to right) 48 - (-3) = 51

= 51

User Vito
by
5.6k points
3 votes

By multiplying 16*3 first, which is 48, then subtract 36 from 48, and finally divide the 12 you get by 12, and the answer is one!

User Mirt
by
5.6k points